No consistent effect of daytime versus night-time measurement of thermal tolerance in nocturnal and diurnal lizards. Issue 1 (20th April 2022) - Dufour, Pauline C; Tsang, Toby P N; Clusella-Trullas, Susana; Bonebrake, Timothy C
Abstract : Thermal tolerance is a critical metric for understanding climate change impacts on biodiversity—but diel variation remains understudied. Across several lizard species in Hong Kong and South Africa, we found no consistent effect of measurement timing (day or night) on thermal tolerance, but one species exhibited a higher daytime critical thermal minimum. Abstract: While essential in understanding impacts of climate change for organisms, diel variation remains an understudied component of temporal variation in thermal tolerance limits [i.e. the critical thermal minimum (CTmin) and maximum (CTmax)]. For example, a higher Ctmax might be expected for an individual if the measurement is taken during the day (when heat stress is most likely to occur) instead of at night. We measured thermal tolerance (Ctmin and Ctmax) during both the daytime and night-time in 101 nocturnal and diurnal geckos and skinks in Hong Kong and in South Africa, representing six species and covering a range of habitats. We found that period of measurement (day vs. night) only affected Ctmin in South Africa (but not in Hong Kong) and that Ctmax was unaffected. Body size and species were important factors for determining Ctmax in Hong Kong and Ctmin in South Africa, respectively. Overall, however, we did not find consistent diel variation of thermal tolerance and suggest that measurements of critical thermal limits may be influenced by timing of measurement—but that such effects, when present, are likely to be context-dependent.